An exploratory study on solar aid relief facilities during flood disasters in Felda areas in Malaysia / Siti Jamiah Tun Jamil and Nur Azfahani Ahmad - Tun Jamil, Siti Jamiah; Ahmad, Nur Azfahani (2021)
Under the Malaysian National Security Council (MKN) Directive Plan No. 20, flood disaster has been recognised as one of the top natural disasters in Malaysia. It is identified in the State Policy and Mechanisms Management report that during flood disasters, electricity supply may be disrupted and people have to face power outage. It leaves them vulnerable, especially if the blackout has occurred for several days. This paper will investigatethe potential of solar technologies as the energy supporter for the flood victims during flood disaster. The energy generated from the photovoltaic (PV) will be operated as the temporary power supply for the focus disaster area. This research has selected FELDA settlements as the focus study. An exploratory study will be obtained to identify the feasibility and the workability of solar technology applications for the flood disaster area